Peran Akuntansi Syariah dalam Membangun Kepercayaan dan Transparansi Keuangan UMKM di Kecamatan Tanete Riattang - Nurfadilah Rahmadani; Zaskia Asmiranda; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The development of Islamic finance has encouraged the implementation of financial management systems based on the values of honesty, justice, and transparency, including in the Micro, Small, and Medium Enterprises (MSMEs) sector. As a strategic sector in the regional economy, MSMEs continue to face various challenges in financial management and reporting, which result in low levels of transparency and trust in business operations. This study aims to analyze the role of Islamic accounting in building trust and enhancing the transparency of MSMEs’ financial reports in Tanete Riattang District. The research employs a qualitative approach using a descriptive method. Data were collected through in-depth interviews with MSME actors and analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of Islamic accounting plays an important role in building financial trust through honest, systematic, and accountable financial recording. In addition, Islamic accounting contributes to improving the transparency of MSMEs’ financial reports through information disclosure, consistency in transaction recording, and ease of access to financial reports for relevant stakeholders. The transparency and trust developed not only affect financial aspects but also foster a work culture that upholds ethical values and responsibility in accordance with the principles of maqāṣid al-syarī‘ah.